Morphological features of atrial myocardium embryonic development and its changes caused by hypoxia effect - Shevchenko, K. M. (Regulatory Mechanisms in Biosystems, 2019)
Mortality and morbidity during the prenatal period of development remain a real problem at the present time. The Scientific Committee EURO-PERISTAT has revealed that mortality of fetuses associated with congenital abnormalities is on average 15–20% across Europe. Hypoxia is one of the top causes of death of fetuses. Since the heart begins to function before birth, influence of teratogenic factors leads to formation of anomalies of its development. Congenital heart defects are the most common of these and occur with a frequency of 24%. Abnormalities associated with the atrium occur with frequency of 6.4 per 10,000 cases. Investigation of structural changes of the atrial myocardium is a key for understanding of pathogenic mechanisms of cardiovascular diseases that are caused by influence of hypoxia. Nowadays, a great deal of research is being dedicated to normal cardiogenesis and much less work is focused on abnormal heart development. There are numerous teratogenic factors such as alcohol, retinoic acid, hyperthermia, hypoxia that are most common causes of heart diseases. The attention of researchers has been predominantly focused on study of changes of the ventricular myocardium under the effect of hypoxia. It is known that the atrium is different from the ventricles by derivation, development and structure. Therefore, the effects of pathological factors on the atrial myocardium will be different as complared to their effect on the ventricles. Also, almost all research has focused on study of consequences of hypoxia at the late stages of cardiogenesis. However, the greatest number of abnormalities is associated with the early embryonic period, as structures that continue development are more sensitive to the effects of harmful factors. Thus, comparative analysis of scientific research devoted to morphological study of atrial myocardium transformations on the cellular and ultrastructural levels under the influence of hypoxia during the stages of cardiogenesis is an important task.